The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1017/s1474747215000438
|View full text |Cite
|
Sign up to set email alerts
|

Early claiming of higher-earning husbands, the survivor benefit, and the incidence of poverty among recent widows

Abstract: Social Security provides survivor benefits to lower-earning spouses of deceased workers entitled to a retirement benefit. The value of the survivor benefit depends on a number of factors including the deceased worker's claim age. We use the Health and Retirement Study and a discrete time hazard model to analyze how the claim age of married men influences the likelihood that their spouse will enter poverty in widowhood. We find that delayed claiming is associated with reduction in a widow's poverty risk. The ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 22 publications
(30 reference statements)
1
5
0
Order By: Relevance
“…The strongest story to emerge from the regression analysis is that husbands make their claiming decisions based on immediate concerns such as workplace pension incentives and health conditions. This conclusion is similar to Henriques (2018) and reinforces the view that Social Security survivor benefits are not a salient consideration when husbands and wives make important decisions about when to retire and claim (Sass et al 2007;Diebold, Moulton, and Scott 2017;and Diebold and Camilleri 2018).…”
Section: Methodssupporting
confidence: 72%
See 1 more Smart Citation
“…The strongest story to emerge from the regression analysis is that husbands make their claiming decisions based on immediate concerns such as workplace pension incentives and health conditions. This conclusion is similar to Henriques (2018) and reinforces the view that Social Security survivor benefits are not a salient consideration when husbands and wives make important decisions about when to retire and claim (Sass et al 2007;Diebold, Moulton, and Scott 2017;and Diebold and Camilleri 2018).…”
Section: Methodssupporting
confidence: 72%
“…In a recent study, Diebold, Moulton, and Scott (2017) show that widows are 6.2 percentage points less likely to fall into poverty if their husbands delay claiming from 62 to 63, and the effect is stronger for widows most reliant on Social Security. Yet, most husbands do not appear to consider survivor benefits when making claiming decisions.…”
Section: Literature Reviewmentioning
confidence: 97%
“…It is possible that the information provided to the men in this Notes: This plot was generated using the coefficients generated from the models that include the full set of controls from Table 3. study fostered a sense of responsibility that they have to financially indemnify their spouse for the reduction in income that would accompany their death. It is possible that men would give additional weight to the survivor benefit information when evaluating their claiming decision if it was combined with information on the financial hardship typically associated with widowhood, as well as information on how dependent widows become on this particular source of income to maintain a level of income above the amount minimally necessary to meet their needs (Diebold et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…The evidence from empirical studies indicates that early claiming by men diminishes the effectiveness of the survivor benefit as an income maintenance mechanism for their widowed spouses. Diebold et al (2017) found that the annual income a widow receives from Social Security is about $650 less for each year that her husband claimed before age 70. Extrapolating from these results, by claiming at age 62 as opposed to age 70, a worker reduces his spouse's annual income in widowhood by $5,200, a substantial sum considering that 42% of widows live in or near poverty (Social Security Administration, 2016 c ).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Delayed claiming of Social Security retirement benefits by men is shown to reduce the poverty risk of their spouse in widowhood (Diebold et al ., 2016). Yet, a series of studies show that the claiming behavior of married men tends to be responsive to the incentives built into their own benefits, but does not always take into account the spouse and survivor benefits: they choose claiming ages that do not maximize the household's and widow's expected present value of benefits (Munnell and Soto, 2005; Sass et al ., 2013; Henriques, 2018).…”
Section: Introductionmentioning
confidence: 99%